2017
DOI: 10.1183/16000617.0095-2017
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension: tailoring treatment to risk in the current era

Abstract: Recent advances in the treatment of pulmonary arterial hypertension (PAH) have led to improved patient outcomes. Multiple PAH therapies are now available and optimising the use of these drugs in clinical practice is vital. In this review, we discuss the management of PAH patients in the context of current treatment guidelines and supporting clinical evidence. In clinical practice, considerable emphasis is placed on the importance of making treatment decisions guided by each patient's risk status, which should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 57 publications
(82 reference statements)
0
31
1
6
Order By: Relevance
“…) is a progressive and incurable disease that occurs when the pulmonary arteries undergo pathological remodelling, causing the blood vessels to vasoconstrict, with a consequent increase in pulmonary vascular resistance. Continued high pressure in the pulmonary artery leads to right ventricular heart failure and death if left untreated (Gaine & McLaughlin, ). Although PAH is a rare disease with an incidence of 15–50 people per million in the population (Humbert et al .…”
Section: Introductionmentioning
confidence: 99%
“…) is a progressive and incurable disease that occurs when the pulmonary arteries undergo pathological remodelling, causing the blood vessels to vasoconstrict, with a consequent increase in pulmonary vascular resistance. Continued high pressure in the pulmonary artery leads to right ventricular heart failure and death if left untreated (Gaine & McLaughlin, ). Although PAH is a rare disease with an incidence of 15–50 people per million in the population (Humbert et al .…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 As a result, combination therapy with ≥ 2 classes of PAH-approved drugs is becoming the standard of care. 2 , 7 In a meta-analysis of 18 randomized controlled trials including 4162 patients with PAH, combination therapy significantly reduced the risk of clinical worsening, significantly increased 6-min walking distance (6MWD) and functional class, and improved hemodynamic parameters compared with monotherapy, although there was no effect on mortality. 8 A second meta-analysis of 17 randomized controlled trials also found a reduction in clinical worsening events with combination therapy versus monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy has been shown to be efficacious in the clinical trial setting, but it may also increase the practical challenges in clinical practice, and care must be taken to ensure that the benefit–risk ratio remains favorable for the patient. The robust clinical efficacy data supporting combination therapy and the role of risk stratification to guide clinical decision-making have recently been comprehensively reviewed [ 9 ]. However, practical advice for healthcare professionals regarding combination therapy management in the clinic is also required.…”
Section: Introductionmentioning
confidence: 99%